Development of Macrophages with Altered Actin Organization in the Absence of MafB - Aziz, Athar (American Society for Microbiology, 2006)
In the hematopoietic system the bZip transcription factor MafB is selectively expressed at high levels in monocytes and macrophages and promotes macrophage differentiation in myeloid progenitors, whereas a dominant-negative allele can inhibit this process. To analyze the requirement of MafB for macrophage development, we generated MafB-deficient mice and, due to their neonatal lethal phenotype, analyzed macrophage differentiation in vitro, in the embryo, and in reconstituted mice. Surprisingly we observed in vitro differentiation of macrophages from E14.5 fetal liver (FL) cells and E18.5 splenocytes. Furthermore we found normal numbers of F4/80(+)/Mac-1(+) macrophages and monocytes in fetal liver, spleen, and blood as well as in bone marrow, spleen, and peritoneum of adult MafB(−/−) FL reconstituted mice. MafB(−/−) macrophages showed intact basic macrophage functions such as phagocytosis of latex beads or Listeria monocytogenes and nitric oxide production in response to lipopolysaccharide. By contrast, MafB(−/−) macrophages expressed increased levels of multiple genes involved in actin organization. Consistent with this, phalloidin staining revealed an altered morphology involving increased numbers of branched protrusions of MafB(−/−) macrophages in response to macrophage colony-stimulating factor. Together these data point to an unexpected redundancy of MafB function in macrophage differentiation and a previously unknown role in actin-dependent macrophage morphology.